(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information on the field of applied art, which reflects the national cultural traditions of our people. Preliminary research on it was reviewed. The lexicon of applied art was briefly analyzed. Information about its history, development, and today’s importance was given.